Indexes and indexing : guide to the indexing of books, and collections of books, periodicals, music, recordings, films and other material, with a reference section and suggestions for further reading - Collison, Robert Lewis (London ; New York : Benn ; De Graff, 1969)
This book sets out to indicate how indexing can make life easier and more efficient, to eliminate time and money wasting and to avoid mistakes and irritation.
Include index
oo 23/01/2019
Loans
Keywords: Indexing